Penerapan Membaca Pemahaman menggunakan Metode Speed Reading dalam Pembelajaran Tematik Terpadu Di Kelas V Sekolah Dasar - Amanata, Ralvi; Taufik, Taufina (Universitas Negeri Padang, 2021)
The writing scientific papers aims to analyze the application of the Speed Reading method in integrated thematic learning seen from the increase in student learning outcomes in elementary schools. This writing is based on the background of the low student learning outcomes in elementary schools because there are still many teachers who do not apply innovative learning models and the application of integrated thematic learning that has not been seen, teachers still use conventional teacher-centered learning models so that students are less active in the learning process. The Speed Reading method is one way to help students so that students can understand the reading text quickly. This scientific writing method uses literature studies (Library Research). By collecting 15 reputable journals with the topic, then analyzing the extent to which student learning outcomes have improved by applying the Speed Reading method. From the results of the data analysis, it shows that the Speed Reading method can improve student learning outcomes with varying amounts of improvement.